The effects of a therapeutic formalin bath on selected immunological and oxidative stress parameters in common carp (Cyprinus carpio) - Hodkovicova, Nikola; Chmelova, Livia; Sehonova, Pavla; Blahova, Jana; Doubkova, Veronika; Plhalova, Lucie; Fiorino, Emma; Vojtek, Libor; Vicenova, Monika; Siroka, Zuzana; Enevova, Vladimira; Dobsikova, Radka; et al. (The Science of the total environment, 2019)
Formalin is commonly used as a component of antiparasitic baths in fisheries. In this study the impact of this bath on the immune profile and oxidative stress parameters was evaluated. A formalin bath was prepared in the concentration of 185.3 mg L-1 (0.17 mL L-1) at a temperature of 20 °C. A total of 96 common carp Cyprinus carpio (Linnaeus, 1758) individuals were immersed in this bath for 60 min. The effects were monitored immediately, and then after 24, 48 h and 10 days following the treatment. The study revealed the most effects 10 days after the treatment, when we observed the decrease of lysozyme in skin mucus, the decrease of anti-inflammatory cytokine transforming growth factor beta in gill tissue and increase of interleukin 10 in cranial kidney tissue. The pro-inflammatory cytokine interleukin 1b showed an increase in gill tissue immediately after the bath and the increase in glutathione peroxidase in gill tissue was also observed 24 h and 10 days after bath treatment. The other investigated parameters did not show any significant changes. In conclusion, even though the formalin bath elevated some parameters as mentioned above, formalin used in the bath is probably safe as an antiparasitic treatment of fish.
Keywords: Animals; Interleukin; Gills; Formaldehyde; oxidační stres; Catalase; interleukin-10; Transforming Growth Factor beta; kapři; Oxidative Stress; Time Factors; formaldehyd; časové faktory; Antiparasitic Agents; transformující růstový faktor beta; žábry; Lysozyme; Interleukin-10; Fish; Interleukin-1beta; antiparazitární látky; Carps; interleukin-1beta; zvířata; Immunoglobulin; Cytokine